Internet-based workplace communications industry & academic applications - St. Amant, Kirk, 1970-; Zemliansky, Pavel. (IGI Global (701 E. Chocolate Avenue, Hershey, Pennsylvania, 17033, USA), 2005)
The essays in this collection advance the project of articulating online workplaces as real and significant, as complex networks of relations that we need to take seriously. The emergent culture of networked communication poses many interesting challenges for researchers, teachers, and writers. In an emergent culture, even the terminologies we use to identify the subject are contested, making it difficult to agree on what we're writing about in the first place, not to mention our reasons for studying it or how we might best meet the challenges it poses.